Sustainable Exploitation of Natural Resources In The European Context: A Comparative Analysis Model - Mihaela Adina MATEESCU; Mihai Sabin MUSCALU; Elena Manuela ISTOC; Daniela Nicoleta BALEANU (Communications of International Proceedings, 2024)
The reserve of natural resources is the main component of the economy. The extraction of natural resources often leads to their inefficient allocation and it generates corruption.  Thus it obtains a negative impact on industrial production and therefore on economic growth.  This paper presents a study to evaluate the position of Romania in relation to the other  EU countries regarding the degree of performance in the exploitation of natural resources during 2020-2022. The purpose of this study is to manage natural resources sustainably and fairly. The paper is based on building synthetic indicators, a complex process that involves the selection of different methods, tools, techniques, and variables.
Keywords: natural resources; sustainable development; analysis model